Methylation risk score of C-reactive protein associates sleep health with related health outcomes - Ziqing Wang; Danielle A. Wallace; Brian W. Spitzer; Tianyi Huang; Kent D. Taylor; Jerome I. Rotter; Stephen S. Rich; Peter Y. Liu; Martha L. Daviglus; Lifang Hou; Alberto R. Ramos; Sonya Kaur; et al. (Communications Biology)
Abstract C-reactive protein (CRP) reflects inflammation status and is linked to poor sleep, metabolic and cardiovascular health. Methylation (MRS) and polygenic risk scores (PRS) reflect long-term systemic inflammation, and genetically-determined CRP, respectively. To refine understanding of inflammation-linked sleep and health outcomes, we construct PRS-CRPs using GWAS summary statistics and a previously-developed MRS-CRP in the Hispanic Community Health Study/Study of Latinos. Via survey-weighted linear regression, we estimate associations between blood-, PRS-, and MRS-CRP, with multiple sleep and health outcomes (n = 2217). MRS-CRP and PRS-CRPs are associated with increasing blood-CRP level by 43% and 23% per standard deviation. MRS-CRP is associated with obstructive sleep apnea (OSA) traits, long sleep duration, diabetes and hypertension, while PRS-CRPs were not. Blood-CRP level is associated with sleep duration and diabetes. Adjusting for MRS-CRP weakens OSA-diabetes/hypertension associations. Consequently, MRS-CRP is a stronger marker than blood-CRP and PRS-CRP to systemic inflammation associated with poor sleep and related comorbidities.